GETUG-AFU 31: a phase I/II multicentre study evaluating the safety and efficacy of salvage stereotactic radiation in patients with intraprostatic tumour recurrence after external radiation therapy—study protocol - Marie-Cécile Le Deley; David Pasquier; Emmanuelle Tresch; Luc Cormier; Martine Duterque; Soazig Nenan; Eric Lartigau (BMJ Open)
Introduction Prostate cancer is the third most important cancer in terms of mortality in men. No standard local treatment exists for patients with an intraprostatic recurrence after radiotherapy. Stereotatic body radiotherapy (SBRT) could be a curative treatment for local recurrence. The phase I/II primary objective is the selection of the recommended dose for salvage-SBRT and to estimate the efficacy.Methods and analysis We plan to perform a multicentre prospective phase I/II study including at least 47 patients. Eligible patients are patients with biochemical recurrence occurring at least 2 years after external radiotherapy for prostatic adenocarcinoma by the Phoenix definition (prostate-specific antigen (PSA) nadir +2 ng/mL) and histologically proven intraprostatic recurrence only (stage T1-T2 on relapse, PSA level ≤10 ng/mL, PSA doubling time >10 months, absence of pelvic or metastatic recurrence proven by choline or PSMA positron emission tomography scan, and pelvic and prostatic assessment by multiparametric MRI). The phase I primary objective is the selection of the recommended dose for salvage-SBRT (5×6, 6×6 or 5×5 Gy) based on dose-limiting toxicity (DLT). The dose of salvage-SBRT will be selected using a time-to-event continual reassessment method based on DLT defined as grade ≥3 gastrointestinal or urinary toxicity or any other grade 4 adverse event. The phase II primary outcome is to estimate the efficacy of the salvage-SBRT in terms of biochemical relapse-free survival rate (Phoenix definition: increase in serum total PSA ≥2 ng/mL above the nadir). Phase II secondary outcomes are acute and late toxicities, quality of life, clinical progression-free survival defined as the time interval between the date of registration and the date of clinical progression or death irrespective of the cause.Ethics and dissemination The study has received ethical approval from the Ethics committee ‘Ile-de-France III’. Academic dissemination will occur through publication and conference presentations.Trial registration number NCT03438552